DESAIN PROGRAM SIMULASI PENERAPAN KODE BOSE CHAUDHURI HOCQUENGHEM PADA DIRECT SEQUENCE SPREAD SPECTRUM - M. Husnul Ullum Azhari; Nyoman Pramaita; I Gst A. Komang Diafari Djuni H (Jurnal SPEKTRUM, 2020)
This study proposes a design of simulation program for implementing Bose ChaudhuriHocquenghem (BCH) code on Direct Sequence Spread Specterum (DSSS) to knowing theperformance of the effect of DSSS with flat fading channel and AWGN without BCH code (7,4)with the application of BCH code (7,4) on DSSS with flat fading and AWGN channel. Thissimulation consist of simulation of BER application of BCH code (7,4) on DSSS with flat fadingand AWGN channel, simulation of BER application code BCH (7,4) on DSSS with AWGNchannel, simulation of the effect of Eb/No on noise variance in the DSSS system, and BERsimulation as a function of noise variance on the DSSS system. Simulation of application BCHcode (7,4) on DSSS with flat fading and AWGN channel analyzed based on Bit Error Rate(BER) versus Energy Bit per Noise (Eb/No). The application of BCH code (7,4) on DSSS withflat fading channel and AWGN shows better performance than DSSS with flat fading channelsand AWGN without BCH coding (7,4). On the Eb/No value 10 dB, simulation application BCHcode (7,4) on DSSS with flat fading channel and AWGN generate BER value which isapproaching 0 with BER value 0.0188, while the DSSS simulation with flat fading channel andAWGN without BCH code (7.4) generate a BER value of 0.0228.